An amine-reactive tetraphenylethylene derivative for protein detection in SDS-PAGE - Yu, Yong (2013)
A new aggregation-induced emission (AIE) compound 1,2-bis[4-(isothiocyanatomethyl)phenyl]-1,2-diphenylethene (2) was synthesized for use in SDS-PAGE. The molecule is practically nonemissive in solution but becomes highly emissive after reacting with the amine groups of the proteins by either the prestaining or poststaining method. The sensitivity of 2 achieved in the prestaining method is the same as that of Coomassie brilliant blue (CBB), while that observed in the poststaining method is higher than that of CBB. Excellent linear responses with the amount of protein were obtained in both cases. The detection of a mixture of proteins with different molecular weights was successfully achieved.